The relation between Hellenic identity and occupied space: Telemachus in Ithaca - Gabrecht, Ana Penha (Romanitas - Revista de Estudos Grecolatinos, 2013)
In this article we will work with the idea that the locations described in the Odyssey, epic poem attributed to Homer, can somehow say something about the way the space was thought and meaning in the ancient Iron Age. We also believe that social interactions performed in the spaces can influence the way in which humans beings understand and represent yourself and others around you. In this sense, the analysis of the adventures of Telemachus (Telemaquia – the first four books of the Odyssey) can help us in the task of understanding the way in which the Greeks understood the place (topos) in which they lived and what makes it a place of identity (isotopia).
Keywords: Odyssey; Homer; Space; Identity; Isotopia